Oficinas psicoeducativas sobre alimentação aos pacientes com diabetes mellitus no ambulatório de diabetes do hospital estadual de Bauru - Carvalho, Rafaela Gonçalves [UNESP]; Mouammar, Christiane Carrijo Eckhardt [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The insulin dependent diabetes mellitu , or type 1 is a chronic disease , and affects approximately one in every five hundred people under twenty years old . ( HOETT 1997) The family's role in adaptation and perception of the child and the diabetes is of utmost importance . The family should feel safe to support the child and transmit the guidelines properly. Adherence to treatment allows control of diabetes and prevention of complications. The World Health Organization suggests regard diabetes, the term " adhesion " refers to the active and voluntary patient involvement in the management of their disease ( MICHELS et al 2010; WHO, 2003). One of the main strategies used to facilitate treatment adherence has been the diabetes education. Through information on the consequences of a bad and a good control, seeks to stimulate the diabetic person to make choices based on what they know. However , it is known in the literature of the area, even in cases where the patient has conscious of the importance of good control of the disease and the consequences of poor control still does not help, and fraud treatment. This is why not just have conscious of the disease and its repercussions, because physical illness directly affects the emotional and this is determined not only by conscious aspects . (GEDD, 2000). The work in question is the result of an extension project , consisting of graduate students in psychology and had its beginning in the year 2013. The current planning of this project is to provide psychoeducational workshops with the theme food for patients and caregivers Diabetes Clinic of the Hospital state of Bauru.

O diabetes mellitus insulinodependente, ou tipo 1, é uma doença crônica, e afeta aproximadamente uma a cada quinhentas pessoas abaixo dos vinte anos de idade. (HOETT,1997) O papel da família na adaptação e na percepção da criança quanto ao diabetes é de extrema importância. A família deve se sentir segura para apoiar a criança e transmitir as orientações de forma adequada. A adesão ao tratamento permite o controle do diabetes mellitus e prevenção de complicações. A Organização Mundial da Saúde propõe, em relação ao diabetes, que o termo “adesão” referese ao envolvimento ativo e voluntário do paciente no manejo de sua doença (Michels et al. 2010; WHO, 2003). Uma das principais estratégias utilizadas para facilitar a adesão ao tratamento tem sido a educação em diabetes. Através de informações sobre as consequências decorrentes de um mau e de um bom controle, procura-se estimular o próprio diabético a fazer suas escolhas a partir daquilo que sabe. No entanto, é sabido pela literatura da área, que mesmo em casos nos quais, o paciente tem consciência da importância de um bom controle sobre a doença, das consequências de um mau controle, ainda assim, não se ajuda e burla o tratamento. Isto ocorre porque não basta ter consciência da doença e suas repercussões, pois a doença física atinge diretamente o emocional e este não é determinado apenas por aspectos conscientes. (GEED, 2000). O trabalho em questão é fruto de um projeto de Extensão, formado por graduandos e psicologia e teve seu início do ano de 2013. O planejamento atual desse projeto é fornecer oficinas psicoeducativas com a temática alimentação, para pacientes e cuidadores do Ambulatório de Diabetes do Hospital Estadual de Bauru.
Keywords: Diabetes mellitus; Psychoeducational workshops; State Hospital of Bauru; Diabetes mellitus; Oficinas psicoeducativas; Hospital Estadual de Bauru